How Service Quality And Communication Interpersonal Affect Customer Satisfaction Making E-Ktp Sukamulya Tangerang - Ari Anggarani Winadi Prasetyoning Tyas; Ummanah Ummanah; Dwi Wahyuningsih (MBIA, 2021)
This study aims to analyze the direct and indirect effect of Service Quality through Interpersonal Communication on Customer Satisfaction in the manufacture of E-KTP in the Sukamulya sub-district, Tangerang. This study involved 240 respondents, analysis of the data using Path Analysis with SEM LISREL data analysis of the customer satisfaction variable as an endogenous variable, interpersonal communication as an intervening variable, service quality variable as an exogenous variable. Sources of data in this study use primary data and secondary data. The study results indicate that the service quality variable directly has a significant effect on customer satisfaction. Interpersonal communication directly has a significant effect on customer satisfaction. Service quality directly has a significant effect on interpersonal communication. Service quality indirectly has a significant effect on customer satisfaction through interpersonal communication. This research implies that Sukamulya Village, Tangerang, in general, needs efforts to maintain and improve customer satisfaction. Through interpersonal communication, efforts to increase customer satisfaction can be made with service quality. Efforts to improve service quality in Sukamulya, Tangerang will strengthen customer satisfaction. Improved interpersonal communication of Sukamulya Sub-district Tangerang employees will be effective in strengthening customer satisfaction if the information provided to the community is appropriate and acceptable Keywords: Interpersonal Communication, Service Quality, Customer Satisfaction, E-KTP Abstrak Penelitian ini bertujuan untuk menganalisis pengaruh langsung dan tidak langsung Service Quality melalui Communication Interpersonal terhadap Customer Satisfaction pada pembuatan E-KTP di kelurahan sukamulya tangerang. Penelitian ini melibatkan 240 responden, analisis terhadap data menggunakan Path Analysis dengan analisis data SEM LISREL terhadap variable customer satisfaction sebagai variable endogen, communication interpersonal sebagai variable intervening, variabel service quality sebagai variable eksogen. Sumber data dalam penelitian ini menggunakan data primer dan data sekunder. Hasil penelitian menunjukkan bahwa variable service quality secara langsung berpengaruh signifikan terhadap customer satisfaction. Commonuciation interpersonal secara langsung berpengaruh signifikan terhadap customer satisfaction. Service quality secara langsung berpengaruh signifikan terhadap communication interpersonal. Service quality secara tidak langsung berpengaruh signifikan terhadap customer satisfaction melalui communication interpersonal. Implikasi dari hasil penelitian ini, Kelurahan sukamulya Tangerang secara umum perlu upaya memelihara dan meningkatkan customer satisfaction. Upaya meningkatkan customer satisfaction dapat dilakukan dengan service quality melalui communication interpersonal. Upaya peningkatan service quality di kelurahan sukamulya tangerang akan efektif memperkuat customer satisfaction. Peningkatan communication interpersonal karyawan kelurahan sukamulya Tangerang akan efektif memperkuat customer satisfaction jika informasi yang diberikan kepada masyarakat sesuai dan dapat diterima. Kata kunci: Interpersonal Communication, Service Quality, Customer Satisfaction, E-KTP